Inclusion of Definitions in Legislative Drafting: A Necessity or a Luxury? - Ezzerouali, Souad; Chami, Yassine (Mazahib, 2023)
Legislative drafting is a crucial element in the formation of legal norms. The success of these norms depends on the accuracy of the words used and the appropriateness of its tools, as it is subject to a set of rules and mechanisms that the legislator must follow, whether at the level of form or at the level of content. Our study will focus on the rule related to using definitions in the exact way to include them in the legislative drafting. It aims to standardize the terms used by the legislator in the legal text in order to avoid any confusion or ambiguity about these terms, and to distinguish it from other meanings that may come in other texts but in a different concepts. The research problem revolves around the extent to which legislation needs to include definitions in laws, is it a necessity or just a luxury? We will address this problem using the descriptive and comparative approach by dividing the study into two parts, the first part deal with the need to include definitions in laws, and the second part addresses the norms governing the use of definitions in legislative drafting. We conclude, that adding a legal definition to the legislative process, giving it legal meaning, would perpetuate the rigid, ossified concept of law. Contrast that with jurisprudential definitions, which sometimes change the true meaning of jurists' terms. However, each definition will be kept in line with the pace of legislation to keep up with the pace of social development, in case it becomes outdated or needs to be supplemented. Keywords: legal drafting, definitions, improvement of law, legal security.